BioSCIENCE: A NEW PROPOSAL FOR OPEN SCIENCE - Malafaia, Osvaldo Andrade (2022)
Academic publishing has undergone many changes with the digital age, making room for new ideas, no longer watertight and associated with the traditional aspects, used for decades, but interactive, modern and with freely accessible possibilities. The objective of this project was to present a new publishing model including, in addition to the traditional aspects, several sections that allow the inclusion of multimedia, infographics, videos, videocasts, postcasts, sounds, images, data publication (data papers), continuing education and university interactivity. A digital review was carried out on the most traditional journals in the medical field, placing the status quo of national and international publishing and raising all the structural needs for the creation of a new model regarding the institutional repository to house all the data and submissions in long term. In conclusion, it was possible to transform a traditional journal with 80 years of continuous publication into a modern project integrated with Open Science and Open Access.